A SOVEREIGN STATE IN THE XXI CENTURY: NEW CHALLENGES AND THREATS - F. I. Valyarovsky (Современная наука и инновации, 2023)
In the article, the author clearly states that the state is the main way of political organization of human society. One of the defining immanent features is State sovereignty. According to the analysis, there are two sides in the structure of state sovereignty – internal and external. The normative content of the external side of state sovereignty is revealed through the generally accepted international legal principles of the sovereign equality of states. The internal side is the completeness of legislative, executive and judicial power under the general concept of "jurisdiction", in exceptional cases regulated by international treaties. The limitations of state sovereignty, as well as threats to state sovereignty, are analyzed, using the example of a challenge to the sovereignty of Russia in connection with the expansion of NATO's influence on the states of Eastern and Central Europe, the activation of terrorist organizations Al-Qaeda, the Taliban, the Islamic State ; "Islamic State"; uncontrolled migrations and other factors related to digitalization. The emergence of illegal and state-controlled sectors of the global computer network Internet, through which illegal DARRNET information is distributed. One of the possible solutions is confrontation – that is, a sovereign state should carefully limit the scope of digital technologies and take measures to ensure their safe use.